Legal Protection and Social Position of National Minorities in Croatia - Mesić, Milan (2003)
The paper elaborates legal protection of minorities in Croatia on the three levels - starting from international minority law and bilateral minority treaties, through the level of the Constitution and the Constitutional Law on Human Rights and Rights of Ethnic or National Minorities, down to special laws and local self-government statutes.